2023
DOI: 10.1186/s12887-023-03944-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experience of family caregivers of children with medical complexity during COVID-19: a qualitative study

Abstract: Background and objectives Children with medical complexity have been disproportionately impacted by the COVID-19 pandemic and the associated changes in healthcare delivery. The primary objective of this study was to gain a thorough understanding of the lived experiences of family caregivers of children with medical complexity during the pandemic. Methods We conducted semi-structured interviews with family caregivers of children with medical complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The parents acknowledged that by actively reducing their child's exposure to the wider community, their child's physical health, but not their mental health, improved. The other literature has reported that enforced isolation during the COVID-19 pandemic resulted in increased mental health issues in children, including stress, depression, and anxiety [63][64][65][66][67]. Further research exploring strategies to accommodate the child's physical health needs without sacrificing child and family emotional health during isolation is needed, in preparation for future pandemics.…”
Section: Highly Skilled Caregivers Delivering Complex Home-based Medi...mentioning
confidence: 99%
“…The parents acknowledged that by actively reducing their child's exposure to the wider community, their child's physical health, but not their mental health, improved. The other literature has reported that enforced isolation during the COVID-19 pandemic resulted in increased mental health issues in children, including stress, depression, and anxiety [63][64][65][66][67]. Further research exploring strategies to accommodate the child's physical health needs without sacrificing child and family emotional health during isolation is needed, in preparation for future pandemics.…”
Section: Highly Skilled Caregivers Delivering Complex Home-based Medi...mentioning
confidence: 99%